Is Early Experience Destiny? Review of Research on Long-Term Outcomes following International Adoption with Special Reference to the British Chinese Adoption Study - Margaret Grant; Alan Rushton; John Simmonds (The Scientific World Journal)
The pathway from adverse early experience to adulthood for internationally adopted children is complex in identifying key influences, impacts, and outcomes. This review arose from the authors’ involvement in the British Chinese Adoption Study, a recent outcomes study that explored the links between early orphanage care, adoptive experiences, and midadulthood. It differs from previous reviews in focusing on a greater length of time since adoption. Both quantitative and qualitative studies were included to allow for examination of a fuller range of adult-related outcomes rather than mental health scores alone. The sampling, methods, and results of reviewed articles are summarised and a critical commentary is provided. Despite methodological differences and identified strengths and weaknesses, conclusions are drawn on the basis of the evidence available. Special attention is paid to the interpretation of negative outcomes. Findings identify areas that should be explored further in order to gain a fuller understanding of midlife outcomes of people who experienced a poor start in life followed by international adoption. Such studies help in refining lifespan developmental theories.